Crimea: The First Step in Russia's Return to the World. Issue 4 (2nd November 2021) - Deliagin, Mikhail
Abstract : The author examines the role of Crimea in the Russian state, beginning with a justification of the legality of the region's annexation as both a reflection of the historical connection between Crimea and Russia and the result of the illegitimacy of the post-coup government in Ukraine. He then turns to the potential role of the integration of Crimea as a national project that could revive Russia while allowing its leaders to root out traitors and other undesirables from among the Russian elites.